Impact of teaching style on procedural learning in Chilean university students - Vega Román, Emmanuel Abraham; Arancibia Ávila, Patricia; Anabalón, Yasna (Journal of Learning Styles, 2025)
Academic performance in higher education can be affected by various factors, including student learning styles and teacher teaching styles. However, the latter, in mainly practical courses, become relevant in the acquisition of skills by students. For this reason, the objective of this study is to evaluate the impact of the teacher's teaching style on the academic performance of university students, with various learning styles, who participated in a practical experience course in oenology. The methodology used is quantitative with a quasi-experimental design, questionnaires on learning and teaching styles were applied, comparing two groups with teachers led by teachers in functional and multiple styles. The results show that the teacher with a functional style favored procedural learning and academic performance, outperforming the group led by the teacher with a multiple style. Despite the initial differences in the students' levels, at the end of the activity, the group with functional teaching showed an improvement in academic performance, understood from the grades.
Keywords: Laboratoy Training; Teaching Styles; Academic Achievement; Higher Education; Learning Style